Skull Base Chordomas and Chondrosarcomas - Kremenevski, Natalia; Schlaffer, Sven-Martin; Coras, Roland; Kinfe, Thomas Mehari; Graillon, Thomas; Buchfelder, Michael (Neuroendocrinology, 2020)
Skull base chordomas account for less than 0.2% and chondrosarcomas for less than 0.15% of all intracranial tumors. Although their clinical and imaging presentations are similar, they derive from different origins. Chordomas arise from embryonic remnants of the primitive notochord and chondrosarcomas from primitive mesenchymal cells or from the embryonic rest of the cranial cartilaginous matrix. Both entities are characterized by infiltration and destruction of the surrounding bone and soft tissue and a high locoregional recurrence rate. Chondrosarcomas, when treated with similar complex strategies, display a much better prognosis than chordomas. The overall survival is approximately 65% for chordomas and 80% for chondrosarcomas at 5 years and 30 and 50%, respectively, at 10 years. Chordomas are divided into the following 3 histological types: classical (conventional), chondroid, and dedifferentiated. Chondrosarcomas have conventional, mesenchymal, clear cell, and dedifferentiated subgroups. Both tumor entities often present with nonspecific symptoms, and headaches are the most reported initial symptom. Computed tomography and magnetic resonance imaging are required to determine the tumor localization and the extent of tumor growth. The treatment philosophy is to maximize tumor resection, minimize morbidity, and preserve function. Neurosurgical approaches commonly used for the resection of intracranial chordomas and chondrosarcomas are transsphenoidal, transbasal, cranio-orbitozygomatic, transzygomatic extended middle fossa, transcondylar, and transmaxillary approaches. Chordomas and chondrosarcomas are not sensitive to chemotherapy and there are no approved drugs for their treatment. The present treatment concept is a combination of surgical resection with a maximal excision and preserving patients' quality of life by adjuvant radiotherapy for both chordomas and chondrosarcomas.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chondrosarcoma; Chordoma; Diagnosis; Skull base; Therapy